Pembinaan Akhlak Konsep Pemikiran Ibnu Miskawaih Sebagai Bentuk Penanggulangan dan Antisipasi Tindak Kriminalitas Remaja - Pratiwi, Nining Ayu (Turast: Jurnal Penelitian dan Pengabdian, 2024)
Criminality is an action taken by a person that is not in accordance with the norms prevailing in society and is also contrary to the law. So that this action gives a person material and psychological losses. Currently, many criminal acts involve teenagers as the perpetrators. This criminal act is disgraceful and contrary to morality. The number of crimes committed by teenagers shows a decline and also a crisis in adolescent morals. Therefore, in tackling and preventing juvenile crime, it is necessary to carry out an act of moral development. The purpose of this study is to find out how moral development is a form of overcoming and anticipating juvenile crime committed by social workers by applying the concept of thinking from Ibnu Miskawaih. The method used in this research is qualitative with a descriptive approach. The results of this study are that social workers act as educators and counselors which in overcoming and preventing crimes committed by adolescents are related to the realm of education. Moral development carried out by social workers in this field is by carrying out habits based on religion such as tausiah, applying smiles, greetings, greetings, being polite and polite and so on. Through this research it was concluded that moral development in adolescents is able to overcome and prevent criminal acts by adolescents. Positive habits that are applied bring youth to a better soul and morals.